Pemanfaatan Koleksi Bank Indonesia Corner sebagai Sumber Informasi bagi Mahasiswa Fakultas Ekonomi di Perpustakaan Universitas Asahan - Rahma Sariva Asdi; Khoirul Jamil; Yusniah Yusniah (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the utilization of the BI Corner collection as a source of information for economics faculty students and to find out what are the obstacles in utilizing the BI Corner collection at the Asahan University Library. This type of research is descriptive qualitative research, namely describing by way of illustrating the use of the BI Corner collection in the library. Informants in this study were 10 people consisting of students of the economics faculty at Asahan University. The data collection techniques in this study were carried out by observation, interviews and documentation. Then the data analysis technique in this study was carried out through three stages, namely data reduction, data presentation and drawing conclusions/verification. While the technique of checking the validity of the data in this study is source triangulation. The results of this study indicate that the use of various BI Corner collections is to meet information needs such as finding references for course assignments and making journal articles. bored while on campus by utilizing the existing facilities at the BI Corner. The obstacles in utilizing the BI Corner collection are the difficulty in finding the required collection because it is not listed in the OPAC, never adding a collection from 2019 so the collection is just that - that's all, there are economics faculty students who don't know the existence of the BI Corner at the Asahan University Library and there is no special librarian who manages the BI Corner so that the management and procurement of BI Corner library materials does not go well. This has resulted in the utilization of the BI Corner collection as a source of information for economics faculty students at the Asahan University Library.